Manipulating scattering of ultracold atoms with light-induced dissipation - Lemeshko, Mikhail (Frontiers in Physics, 2013)
Recently it has been shown that pairs of atoms can form metastable bonds due to non-conservative forces induced by dissipation [Lemeshko and Weimer, Nature Comm. 4, 2230 (2013)]. Here we study the dynamics of interaction-induced coherent population trapping—the process responsible for the formation of dissipatively bound molecules. We derive the effective dissipative potentials induced between ultracold atoms by laser light, and study the time evolution of the scattering states. We demonstrate that binding occurs on short timescales of 10 μs, even if the initial kinetic energy of the atoms significantly exceeds the depth of the dissipative potential. Dissipatively-bound molecules with preordained bond lengths and vibrational wavefunctions can be created and detected in current experiments with ultracold atoms.